Regenerative Capacity of the Upside-down Jellyfish Cassiopea xamachana - Gamero-Mora, Edgar (Zool Stud, 2019)
This study provides the first observation that umbrellar tissue can lead to the formation of virtually all body structures in jellyfish of the order Rhizostomeae. The regeneration process was observed in two specimens of the upside-down jellyfish Cassiopea xamachana Bigelow, 1892, one housed at the Vienna Zoo, Austria and the other in a laboratory at the University of São Paulo, Brazil. The process was triggered by an injury and ended with the formation of two new sets of body structures. Our observation offers evidence that C. xamachana has a hidden regenerative capacity exceeding that previously recorded.